IDEOLOGI DI BALIK PIDATO KENEGARAAN PERINGATAN MASIRAT AL-HADRAA KE-49 - Siroj, Muhammad Sidqon (Multikultura, 2026)
This study examines the 49th anniversary speech of the Green March (Masirat Al-Hadraa) as an ideological instrument within the political framework of the Kingdom of Morocco. The research reveals that the historical narrative of the Green March is reproduced not merely as collective memory, but as a strategic mechanism to consolidate monarchical legitimacy and assert territorial sovereignty over Western Sahara. Utilizing a qualitative methodology grounded in Fairclough’s Critical Discourse Analysis (CDA), the findings demonstrate that King Mohammed VI’s discourse serves three primary functions: first, reinforcing the monarchy’s historical-religious and institutional authority amidst domestic and regional political pressures; second, reconstructing a Moroccan national identity that is inherently tied to the territorial integrity of Western Sahara; and third, neutralizing oppositional narratives specifically from the Polisario Front and Algeria by framing Moroccan sovereignty as the sole legitimate political reality. This study contributes to the field of Arabic Discourse Studies by dissecting the discursive operations of power hegemony.